The Effect of Competency and Motivation of Work Satisfaction and its Implementation of Lecturer Commitments in the Private Vocational School of Lldikti Area IV in Banten - Permana, Angrian; Aima, M. Havidz; Ariyanto, Eny; Syafarudin, Afriapollo (International Review of Management and Marketing, 2019)
This study aims to determine the effect of competence on lecturer job satisfaction, motivation on lecturer job satisfaction, competence on lecturer work commitments, motivation on lecturer work commitments, and job satisfaction on lecturer work commitments at Private Universities in Banten Province. This research uses quantitative methods with a total sample of 330 people. Samples were taken from a lecturer population spread across several private universities in Banten, namely, Serang City, South Tangerang City, Tangerang City, Tangerang Regency, Pandeglang Regency, Lebak Regency, and Cilegon City. The analytical tool used in this study uses SEM with the Smart PLS tool. The results of this study are competence influences lecturer job satisfaction, motivation influences lecturer job satisfaction, competence influences lecturer work commitment, motivation does not affect lecturer work commitment, and satisfaction influences lecturer work commitment. Keywords: Competence, Motivation, Job Satisfaction, Work Commitment JEL Classification: J28 DOI: https://doi.org/10.32479/irmm.8833